Biliverdin–copper complex at physiological pH. Issue 18 (8th February 2019) - Dimitrijević, Milena S.; Bogdanović Pristov, Jelena; Žižić, Milan; Stanković, Dalibor M.; Bajuk-Bogdanović, Danica; Stanić, Marina; Spasić, Snežana; Hagen, Wilfred; Spasojević, Ivan
Abstract : In physiological settings, biliverdin and Cu 2+ build a paramagnetic complex with formal structure: radical cation/Cu 1+ or radical anion/Cu 3+ . Abstract : Biliverdin (BV), a product of heme catabolism, is known to interact with transition metals, but the details of such interactions under physiological conditions are scarce. Herein, we examined coordinate/redox interactions of BV with Cu 2+ in phosphate buffer at pH 7.4, using spectrophotometry, HESI-MS, Raman spectroscopy, 1 H NMR, EPR, fluorimetry, and electrochemical methods. BV formed a stable coordination complex with copper in 1 : 1 stoichiometry. The structure of BV was more planar and energetically stable in the complex. The complex showed strong paramagnetic effects that were attributed to an unpaired delocalized e − . The delocalized electron may come from BV or Cu 2+, so the complex is formally composed either of BV radical cation and Cu 1+ or of BV radical anion and Cu 3+ . The complex underwent oxidation only in the presence of both O2 and an excess of Cu 2+, or a strong oxidizing agent, and it was resistant to reducing agents. The biological effects of the stable BV metallocomplex containing a delocalized unpaired electron should be further examined, and may provide an answer to the long-standing question of high energy investment in the catabolism of BV, which represents a relatively harmless molecule per se .